Оптимизация энергетического баланса ветрогенератора - Neuberger, Nikolaus; Nolle, Eugen; Banschbach, Rolf; Пивняк, Геннадий Григорьевич; Бешта, Александр Степанович (НТУ "ХПИ", 2010)
The paper deals with energy balance in wind power generating installations. It is shown that due to variations of speed and direction of the wind the local power generating installations with energy accumulating components are especially subdued to instability. A control system is developed for maintenance of optimal power mode. The system implements cubic dependence of the output power of frequency. The algorithm of optimal power control is offered, its digital implementation is described. The article is targeted at specialists in small wind turbines.
Wind turbine energy performances optimization
Keywords: мощность; момент крутящий; числовое программное управления; ПИД-регулятор